1983
DOI: 10.1038/304699a0
|View full text |Cite
|
Sign up to set email alerts
|

Priming for and induction of anti-poliovirus neutralizing antibodies by synthetic peptides

Abstract: Five peptides containing amino acid sequences from the type 1 poliovirus structural protein VP1 have been synthesized. Each of the peptides was found capable of priming the immune system of rabbits for a long-lasting, virus-neutralizing IgG antibody response following a single inoculation of intact virus. One peptide directly induced the production of neutralizing antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
2

Year Published

1984
1984
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(138 citation statements)
references
References 31 publications
7
129
2
Order By: Relevance
“…2). This sequence, conserved in all FCV isolates so far examined, is an area that according to computer analysis (Emini et al, 1985) contains a hydrophilic region of high surface probability surrounded by hydrophobic regions with low surface probability. These conserved amino acids might possibly be involved with virus attachment with the hydrophilic portion surrounded by hydrophobic areas providing a 'canyon' for virus attachment similar to the situation of rhinovirus binding (Rossmann et al, 1985).…”
Section: S ! O C F Cmentioning
confidence: 99%
“…2). This sequence, conserved in all FCV isolates so far examined, is an area that according to computer analysis (Emini et al, 1985) contains a hydrophilic region of high surface probability surrounded by hydrophobic regions with low surface probability. These conserved amino acids might possibly be involved with virus attachment with the hydrophilic portion surrounded by hydrophobic areas providing a 'canyon' for virus attachment similar to the situation of rhinovirus binding (Rossmann et al, 1985).…”
Section: S ! O C F Cmentioning
confidence: 99%
“…After virus challenge, titres of gp70 antibodies increased drastically only in the pepl-KLH group. Similar priming by immunization with synthetic peptides has been reported after immunization against poliovirus or foot-and-mouth disease virus using synthetic vaccines (Emini et al, 1983;Francis et al, 1985).…”
Section: Multi-peptide Vaccines But Not Single-peptide Vaccines Incrementioning
confidence: 78%
“…The cDNA fragment introduced into vaccinia virus has the complete coding sequence of VP4, VP2 and VP3, and the N-terminal 57 amino acids of VP1. This N-terminal portion of VP1 would, therefore, also incorporate the epitope described by Emini et al (1985) and, as shown by the immunoblot experiments, the VP1 peptide antibody to this epitope binds to the expressed HAV polyprotein.…”
Section: Discussionmentioning
confidence: 99%